Ethical Practices and Efficiency in the Internal Control of Peruvian Public Transport - Banda, Alexandra Carolina Dávila; Agip, Lisby Nayely Ramirez; Rodríguez, Víctor Hugo Puican (Journal of Ecohumanism, 2024)
The study aims to assess the impact of ethical practices on the effectiveness of internal control in public transport companies in Peru, to understand how these aspects influence corporate integrity, customer trust and corporate reputation; a quantitative, descriptive and explanatory methodology was used; data were collected through structured surveys applied to 50 employees of a transport company, covering various areas such as sales, administration and internal control; it is concluded that ethical practices significantly influence the effectiveness of internal control. Deficiencies in these areas lead to loss of customer confidence and financial and legal risks. The integration of sound ethical practices into business culture and processes improves management, customer confidence and business sustainability; highlights the need to improve integrity and operational efficiency in transport companies. It recommends implementing ethics training programmers and strengthening internal control systems adapted to the local context, as well as integrating advanced technologies for risk management and visualization.Corporate Governance